Fiji : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix examines the relationship between investment and long-term growth in Fiji. It reviews Fijian data, and indicates that the slowdown in the growth rate since independence has been associated with a decline in investment, particularly by the private sector. The paper reviews empirical research on the link between investment and growth, and presents additional evidence for the linkage in the context of Small Island Economies (SIEs) in which tourism plays a major role.